The Archaeology of Kinship : Advancing Interpretation and Contributions to Theory - Ensor, Bradley E., 1966- (Book collections on Project MUSE., 2013)
"Bradley Ensor shows how kinship can be a valuable tool for archaeologists. The Archaeology of Kinship explains how kinship is relevant to contemporary archaeological theory, detailing methods appropriate for archaeological analysis, and provides long-overdue solutions to problems plaguing ethnological hypotheses on the origins and contexts of kinship behaviors"--Provided by publisher.